The Influence of the Picture and Picture Model Assisted by Video Media on the Problem Solving Ability and Mathematics Learning Motivation of Students at SDN 100312 Pargarutan Jae South Tapanuli - Doharni, Hasnah; Hasratuddin, Hasratuddin; Husein, Rahmad; Syahril, Syahril (Pusdikra Publishing, 2025)
The research aims to analyze differences in students' mathematical problem solving abilities through the picture and picture learning model assisted by media and given regular learning, analyze differences in students' mathematics learning motivation through the picture and picture learning model assisted by video media and given regular learning, analyze the interaction between learning and ability students' initial abilities on students' mathematical problem solving abilities, and analyzing the interaction between learning and students' initial abilities on students' mathematics learning motivation at SDN 100312 Pargarutan Jae Tapanuli Selatan. The sample was determined as 62 people consisting of 2 (two) classes. The research design used in this research is an experimental design with a 2x3 factorial. The results of the research concluded that students' mathematical problem-solving abilities through the picture and picture learning model assisted by video media were better than if they were given regular learning at SD Negeri 100312 Pargarut.an Jae Tapanuli Selatan. Students' motivation to learn mathematics through the picture and picture learning model assisted by video media is better than being given regular learning at SD Negeri 100312 Pargarutan Jae Tapanuli Selatan. There is an interaction between learning and students' initial abilities on students' mathematical problem-solving abilities at SD Negeri 100312 Pargarutan Jae Tapanuli Selatan. There is an interaction between learning and students' initial abilities on students' mathematics learning motivation at SD Negeri 100312 Pargarutan Jae Tapanuli Selatan.